2021
DOI: 10.3389/fmed.2021.753220
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Therapy Reduces the Severity of Placental Lesions in Chronic Histiocytic Intervillositis

Abstract: Chronic histiocytic intervillositis (CHI) is a rare, but highly recurrent inflammatory placental lesion wherein maternal macrophages infiltrate the intervillous space. Pregnancies with CHI are at high risk of fetal growth restriction, miscarriage or stillbirth. Presently, the diagnosis can only be made after histopathological examination of the placenta. Given its proposed immunological etiology, current treatments include aspirin, heparin, and immunomodulatory agents. However, the rationale for these medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…This combination significantly reduced histological severity of CHI: in the index pregnancy, 11/28 (39%) cases were mild, 11/28 (39%) were moderate and 6/28 (21%) were severe; whereas in subsequent pregnancies treated with prednisolone and/or hydroxychloroquine, CHI was absent in 18/30 (60%) and only severe in 2/30 (7%). It also translated into a non-significant trend towards higher rates of live birth in the prednisolone and/or hydroxychloroquine group, compared with those who received non-immunomodulatory treatment: 25/29 (86%) vs. 8/13 (62%), p=0.11 (179).…”
Section: Immunosuppression To Prevent Recurrent Adverse Pregnancy Out...mentioning
confidence: 98%
See 3 more Smart Citations
“…This combination significantly reduced histological severity of CHI: in the index pregnancy, 11/28 (39%) cases were mild, 11/28 (39%) were moderate and 6/28 (21%) were severe; whereas in subsequent pregnancies treated with prednisolone and/or hydroxychloroquine, CHI was absent in 18/30 (60%) and only severe in 2/30 (7%). It also translated into a non-significant trend towards higher rates of live birth in the prednisolone and/or hydroxychloroquine group, compared with those who received non-immunomodulatory treatment: 25/29 (86%) vs. 8/13 (62%), p=0.11 (179).…”
Section: Immunosuppression To Prevent Recurrent Adverse Pregnancy Out...mentioning
confidence: 98%
“…A large Canadian series analysed almost 30,000 placentas and reported a prevalence of 0.17% (10). However, CHI and VUE frequently coexist (179): in the first account of CHI published by Labarrere & Mullen in 1987, it was described as an "extreme variant" of VUE (17). Nowak et al, who reported outcomes from 76 cases of combined CHI-VUE, suggested that CHI might represent either a precursor lesion or a more aggressive variant of VUE (25).…”
Section: Chronic Histiocytic Intervillositis (Chi) Chi: Definition Pr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although evidence regarding therapeutic interventions for CHI are few and far between, a small number of studies have suggested that thromboprophylactic drugs, such as aspirin and heparin, as well agents targeting the immune system, including hydroxychloroquine and glucocorticoids, may be of therapeutic benefit which is consistent with immunologic origin of the disease and the potential role of anti-human platelet antigen antigen-1a in induction of low-grade CHI (8,9). For instance, hydroxychloroquine and prednisolone were associated with 62% improvement in live birth rate compared to untreated pregnancies (8). Furthermore, heterogenous combinations of all of the aforementioned agents in a multicenter study by Melkinian et al led to the increased number of live births from 32 to 67%.…”
Section: Therapeutic Interventionsmentioning
confidence: 97%